How AI-Augmented Training Improves Worker Productivity - Didier Fouarge; Marie-Christine Fregin; Simon Janssen; Mark Levels; Raymond Montizaan; Pelin Özgül; Nicholas Rounding; Michael Stops (Institute of Labor Economics (IZA), 2025)
We analyze the impact of AI-augmented training on worker productivity in a financial services company. The company introduced an AI tool that provides performance feedback on call center agents to guide their training. To estimate causal effects, we exploit the staggered roll out of the AI-tool. The AI-augmented training reduces call handling time by 10 percent. We find larger effects for short-tenured workers because they spend less time putting clients on hold. But the AI-augmented training also improves communication style with relatively stronger effects for long-tenured agents, and we find slightly positive effects on customer satisfaction.
Keywords: J24; O31; O33; 330; artificial intelligence; training; performance feedback; employee productivity